HUBUNGAN MUTU LAYANAN KEBIDANAN DENGAN KEPUASAN IBU NIFAS - ROSPIA, EVI DILIANA (Jurnal Kesehatan Abdurrahman, 2025)
Background: The quality of health services shows the level of health services in creating a sense of satisfaction in each patient. The more perfect the satisfaction, the better the quality of health services. Subjective patient satisfaction will influence the implementation of service quality. Objective: To analyze the relationship between the quality of midwifery services and the satisfaction of postpartum mothers in the Gangga Community Health Center Working Area. Method: This research uses quantitative research, with a cross-sectional research design approach. The population in the study was 45 postpartum mothers and the sampling technique used total sampling. The research sample will fill out a questionnaire regarding the quality of midwifery services and satisfaction of postpartum mothers at the Puskesmas, then the data that has been collected will be analyzed using chi-square, to analyze whether there is a relationship between the quality of midwifery services and the satisfaction of postpartum mothers. Results: The research results showed that the characteristics of the majority of respondents were postpartum mothers aged 20-35 years, namely 34 respondents (75.6%). The majority of postpartum mothers had moderate education, 32 respondents (71.1%). The majority of postpartum mothers were multiparous with 31 respondents (68.9%). The majority of postpartum mothers do not work, 35 respondents (77.8%), the average quality of midwifery services is in the good category, 39 respondents (86.7%), while the majority of postpartum mothers' health service satisfaction is in the satisfied category, 43 respondents (95.6%). Bivariate tests showed that responsiveness, physical evidence, service quality assurance were related to satisfaction with maternal health services during the postpartum period, while aspects of empathy, reliability and service quality were not related to satisfaction with postpartum mothers.